Crystal structure refinement of pseudojohannite, Cu3(OH)2[(UO2)4O4(SO4)2](H2O)12, from the type locality - Jachymov, Czech Republic - Plasil,J. (Journal of Geosciences, 2015)
The crystal structure of pseudojohannite from the type locality, Jachymov (Western Bohemia, Czech Republic), was solved by charge-flipping method from single-crystal X ray diffraction data and refined to an R = 0.0385 against 2072 unique observed reflections. Pseudojohannite from Jachymov is triclinic, P 1, with a = 8.6653(4), b = 8.8499(5) Å, c = 9.9908(6), α = 72.103(6), β = 70.512(5)°, γ = 76.070(5)°, V = 679.12(7) Å3 and Z = 1. The structural formula derived from the refinement and bond-valence considerations is Cu3(OH)2[(UO2)4O4(SO4)2](H2O)12, confirming previous structure determination on the material from Widowmaker mine, Utah, USA. Contrary to other members of the zippeite-group, the interstitial metal sites in pseudojohannite (populated by Cu2+), are fully occupied and the structure tends to be fully ordered with no important departure from the ideal stoichiometry.
Keywords: pseudojohannite; uranyl sulphate; zippetite group; crystal structure; Jachymov